EXPRESSION OF THE WHEAT LEAF RUST RESISTANCE GENE LR34 ALONEAND IN COMBINATION WITH OTHER LEAF RUST GENES AGAINST UKISOLATES OF PUCCINIA TRITICINA - Abdul, S D (Emirates Journal of Food and Agriculture, 2011)
Wheat cultivars and ?Thatcher’ backcross lines with the resistance gene Lr34 alone and in combination with different genes for leaf rust resistance were assessed for their reaction to UK isolates of Puccinia triticina. The experiments were conducted in controlled environments and in the field. The seedlings were grown at 5 and 200 C and as adult plants at 12 and 260 C. The temperature control was used to identify the Lr34 gene. In the field, all lines and cultivars with Lr34 were resistant to leaf rust. In controlled environments, seedlings with Lr34 alone gave variable infection types (ITs) of ; to 3 at 50 C and 2 to 3- at 200 C. This indicates that, temperature control is not effective at identifying the Lr34 gene with these UK isolates. Based on similarities of reaction types in the field, the wheat cultivars Pavon 76, Ciano 67, Chris, Era and Marco Juarez Inta were postulated as having the resistance gene Lr34.